Projeto de correção de uma plataforma com dois graus de liberdade - Pelogia, Renan Aparecido (2019)
Stability is a concept present in many equipments and it’s essential to safety, comfort and good results in these applications. This work contemplates the design of a system consisting of two plates, one inferior that is affected by a series of perturbations, and one superior initially parallel to the inferior, both connected by a bar. The system also have a controller whose purpose is to keep the top plate in the desired position regardless of the imposed movement on the lower plate. This project can be applied in systems where there are many undesirable disturbances, such as vehicles traveling on irregular roads, wheelchairs capable of correcting the position of their seat when on steep ramps and abrupt shifts of terrain in general. The board control uses classic control techniques applied to current technologies such as microcontrollers and servo motors.